Characteristics of the Zikir Zawiyah Derived by the Prophet and Its Influence on the Socio-Religious Congregation - Mabila Azzahra; Lukman Hakim; Muhammad Arifin; Muhammad Ash Shiddiqi (Islamic Studies and Civilization Journal, 2025)
The practice of dhikr is a fundamental element in Islamic spirituality which plays an important role in building a relationship between humans and Allah (ḥablum minallah) while strengthening social relations between each other (ḥablum minannas). Amidst the dynamics of modern society characterized by increasingly complex social changes and spiritual needs, studies on the role of dhikr in socio-religious life are still relatively limited, particularly in local tarekat communities. This study aims to analyze the characteristics of dhikr practices at Zawiyah Nurun Nabi and their influence on the socio-religious life of the congregation. This study uses a qualitative approach with ethnographic methods through participatory observation, in-depth interviews with zawiyah administrators and congregation members, and documentation of dhikr activities and social interactions. The results show that dhikr practices at Zawiyah Nurun Nabi contribute significantly to improving emotional well-being, inner peace, and the quality of worship of the congregation. In addition, collective dhikr strengthens social solidarity, increasing empathy, patience, and cooperation among congregation members. These findings confirm that dhikr not only has a spiritual dimension but also functions as an effective instrument of socio-religious development in forming a harmonious and empowered Muslim community.